2015
DOI: 10.1007/s10522-015-9572-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dietary fat source on liver and skeletal muscle mitochondrial modifications and lifespan changes in calorie-restricted mice

Abstract: The Membrane Theory of Aging proposes that lifespan is inversely related to the level of unsaturation in membrane phospholipids. Calorie restriction (CR) without malnutrition extends lifespan in many model organisms, which may be related to alterations in membrane phospholipids fatty acids. During the last few years our research focused on studying how altering the predominant fat source affects the outcome of CR in mice. We have established four dietary groups: one control group fed 95% of a pre-determined ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 140 publications
(200 reference statements)
1
8
0
Order By: Relevance
“…Hyperinsulinemic compensation has been hypothesized to be a normal response to insulin resistance . Hyperinsulinemia can be driven by changes in insulin secretion and/or insulin clearance .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperinsulinemic compensation has been hypothesized to be a normal response to insulin resistance . Hyperinsulinemia can be driven by changes in insulin secretion and/or insulin clearance .…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, mitochondria can adapt to a saturated fat diet by reducing proton leak, whereas proton leak is increased with diets high in omega-3 PUFAs (26), resulting in differential effects of these dietary fats on energy conservation and expenditure. In addition, there are distinct effects of dietary fat on mitochondrial enzyme activity, fission proteins, and apoptotic signaling (26); however, we did not investigate these mechanisms of insulin resistance in the current study.…”
Section: Obesitymentioning
confidence: 92%
“…Nevertheless, we have previously shown that mitochondrial phospholipid fatty acid composition was altered in liver and skeletal muscle from CR mice in a manner that reflected the unsaturated fatty acid composition of the diet with the consequent increase of n‐3 and n‐6 fatty acids in CRF‐ and CRS‐fed animals, respectively, and probably changing several properties of the membranes (Chen et al ., 2012, 2013). On the other hand, CRL‐fed animals showed a significantly higher proportion of mitochondrial monounsaturated fatty acids (especially oleic acid), a result that was accompanied by improved mitochondrial functions and ultrastructure (see Villalba et al ., 2015 for a recent review). Thus, it is very likely that an increase in monounsaturated fatty acids such as oleic acid may be involved in the beneficial effect of lard as a dietary fat in CR‐fed animals.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy rats, it was demonstrated that dietary lipids alter the fatty acid (FA) profile of mitochondrial membrane in multiple tissues, including skeletal muscle, which may elicit short- or long-term changes in reactive oxygen species (ROS) production by muscle mitochondria in muscle-specific manner. 26 , 27 Namely, 8 weeks of diet with 15% fat derived from soybean oil (n-6 PUFA-rich) or coconut oil (saturated FA-rich) resulted in changed activities of some antioxidant enzymes in muscle-specific manner. 27 Interestingly, despite the diverse activity of ROS scavenging enzymes found in SOL and white gastrocnemius muscles after both high fat diets, an increased lipid peroxidation was found in both muscles.…”
Section: Discussionmentioning
confidence: 99%